2011
DOI: 10.1002/app.34677
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy toughening using low viscosity liquid diglycidyl ether of ethoxylated bisphenol‐A

Abstract: Two new epoxy resins, diglycidyl ether of ethoxylated bisphenol-A (BPA) with two and six oxyethylene units (DGEBAEO-2 and DGEBAEO-6) were synthesized and characterized. DGEBAEO-6 was used to toughen the conventional epoxy resin diglycidyl ether of BPA (DGEBA). The blends of DGEBA with different amounts of DGEBAEO-6 were cured by 4,4 0 -diamino diphenylmethane (DDM), and their thermal and mechanical properties were examined. The DSC and DMA results presented that DGEBA/DGEBAEO-6 blends exhibited a homogenous ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Zhang and coworker find that incorporation of hyperbranched polyesters with rigid aromatic rings into DGEBA increases the tensile strength of cured resins to a certain extent [10] . Yang and coworkers studied the effects of the length of oxyethylene units in linear epoxy resin and showed that strength and modulus can be maintained if enough crosslinking sites and rigid aromatic rings exist in the curing system [26] . In this study, aromatic rings from A 2 monomer provide rigidity for HBPEE.…”
Section: Mechanical Properties Of the Cured Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and coworker find that incorporation of hyperbranched polyesters with rigid aromatic rings into DGEBA increases the tensile strength of cured resins to a certain extent [10] . Yang and coworkers studied the effects of the length of oxyethylene units in linear epoxy resin and showed that strength and modulus can be maintained if enough crosslinking sites and rigid aromatic rings exist in the curing system [26] . In this study, aromatic rings from A 2 monomer provide rigidity for HBPEE.…”
Section: Mechanical Properties Of the Cured Hybridsmentioning
confidence: 99%
“…As a result, addition of HBPEE (≤ 20 wt%) does not compromise the tensile strength of cured hybrids if properly cured. and showed that the impact strength of cured resins is directly proportional to the oxyethylene content [26] . As a result, abundant flexible aliphatic units in HBPEE can contribute to the toughness of cured hybrids.…”
Section: Mechanical Properties Of the Cured Hybridsmentioning
confidence: 99%
“…1,2 The toughening of epoxy materials is very important and has long been the focus of many research investigations [3][4][5][6][7] . However, the application of epoxy materials is often limited by their intrinsic brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…The studies about the chemical structural modification of epoxy resins have recently attracted much attention in attempts to enhance fracture toughness, T g , and thermal properties simultaneously . Kaji et al .…”
Section: Introductionmentioning
confidence: 99%
“…The epoxy blend containing 75 wt % DGEBA and 25 wt % TGBAPB showed a significant increase in both toughness and stiffness, which resulted from the synergistic effect of the rigid aromatic rings and the flexible ether linkages. DGEBA has also been modified by diglycidyl ether of ethoxylated bisphenol‐A containing six oxyethylene units (DGEBAEO‐6) . When 50 wt % DGEBAEO‐6 was added, the impact strength of the cured blend reached five times higher than that of pure DGEBA, and the network toughening mechanism of plastic deformation was proposed.…”
Section: Introductionmentioning
confidence: 99%